Răspuns :
1) [1/(x+1)+1/2(x+1)]·(x-1)(x+1) /3
=3 / 2(x+1) ·(x+1)(x-1)=(x-1) / 2
2)E(x)=[x / (x-1)(x+1) -1/(x+1)]·(x-1)²
=1 /(x-1)(x+1) ·(x-1)²
=(x-1) / (x+1)
=3 / 2(x+1) ·(x+1)(x-1)=(x-1) / 2
2)E(x)=[x / (x-1)(x+1) -1/(x+1)]·(x-1)²
=1 /(x-1)(x+1) ·(x-1)²
=(x-1) / (x+1)
1.[1/(x+1) +1/2(x+1)].(x²-1)/3
aducand la numitorul comun 2(x+1)
[(2+1)/2(x+1)].(x-1)(x+1)/3=
3/2(x+1) ·(x+1)(x-1)/3=
(x-1)/2
2.[x/(x-1)(x+1) -1/(x+1)]·(x-1)²=
numitor comun (x-1)(x+1)
[(x-x+1)/(x-1)(x+1)]·(x-1)²=1/(x-1)(x+1) ·(x-1)²=(x-1)/(x+1)
unde /-fractie
aducand la numitorul comun 2(x+1)
[(2+1)/2(x+1)].(x-1)(x+1)/3=
3/2(x+1) ·(x+1)(x-1)/3=
(x-1)/2
2.[x/(x-1)(x+1) -1/(x+1)]·(x-1)²=
numitor comun (x-1)(x+1)
[(x-x+1)/(x-1)(x+1)]·(x-1)²=1/(x-1)(x+1) ·(x-1)²=(x-1)/(x+1)
unde /-fractie